Individuals And Society in Liquid Modernity - Suzan Sabri (QALAAI ZANIST JOURNAL, 2021)
Liquid modernity might be a new concept for many. According to sociologist and philosopher Zygmunt Bauman, modern society is melting and becoming fluid as he defines the latter as Liquid modernity. In his work, Bauman analyses the disappearance of solid structures and institutions that formed the foundation of modern society in which they are increasingly making way for processes that are constantly changing. In addition, this fluid world never retains the same shape for long and is characterized by never standing still. Everything seems to change: the fashion we follow, the technology we use, and the things we dream of. This results in constant uncertainty and fear of what the future holds. This new order, which is a continuation of modernity in a different form offers opportunities. Especially, that current time and place are losing relevance due to technological developments and in this way the world is at the feet of the fluid individual. Bauman labels the latter as ‘change is the only constant and uncertainty is the only certainty’(Bauman, 2012). The aim of this study is to elaborate the above stated changes that affect individuals and society in terms of becoming fluid. Besides, it is worth mentioning that identities are complex and constantly changing. Complexity influences the power and politics in modern societies in relation to the globalized era. In other words, there is an increasing gap between the ability to act effectively (power) and the ability to decide what should be done (politics).